Recursive holistic asset and liability management (GHAP) model to optimize economic and financial results in the municipal savings and credit banks (CMACS) of Peru - 2009 - Carita Monroy, Fidel (2012)
This research work proposes a modcl for dircction and management that allows optimize the profíts of capital invested as a result of an adequate management of active and poassive capital flow in the core of business: receptions and collocations. In the last 10 years CMACS in Peru have shown a decrease in profitability, that is why it is necessary to implement a model to allow the correction of such problem. In this connection we propose the GHAP model as a holistic, systemic and continuing process in its structure and each of its parts. It fulfills the model of an integral perspective (a whole) which is ordered and iterative. This is an ergodic and autopoietic model. It is established and founded on three main components: processes, networks and functional structures as well as recursivity.